صفات الخوارج في السنة النبوية = Characteristics of the kharijite sects in the prophetic sunnah - Marzoqi, Salman Muhammad Abdullah; Gasmelsid, Saadeldin Mansour (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2018)
الخوارج هي أول فرقة ظهرت في التاريخ الإسلامي، وقد حذر منها النبي صلى الله عليه وسلم، ولها أفكار ومعتقدات بعيدة عن الهدي النبوي، فهي تقوم على: تكفير المسلمين، والخروج عن طاعة ولي الأمر، واستباحة دماء المسلمين. ولقد بدأت فتنة الخوارج مبكرا منذ عهد النبوة، مرورا بعصر الخلفاء الراشدين وحتى يومنا هذا، ولا تزال كذلك حتى قيام الساعة. وفي هذا البحث نحاول جمع الأحاديث الواردة فيهم، واستخلاص صفاتهم منها، مع ذكر بعض الفوائد **************************************************** Al-Khawarij is the first group to appear in Islamic history. The Prophet (peace and blessings of Allah be upon him) warned about it. It has ideas and beliefs far from the Prophetic guidance. It is based on: declaring Muslims as Kafirs, breaking the obedience of the ruler, and killing the Muslims who disagree with them, as they consider them non-Muslims. The Kharijite sects began early in the time of the Prophethood, the era of the Caliphs until today, and continues until the Final Hour of the World. In this research we shall try to collect the ahadith about them, extract their qualities from them, and attempt to write some benefits and lessons for today.